The relationship between working environment and administrative support staff's productivity at IADA Kalaka-Saribas, Saratok / Muhamad Afiq Abdul Kadir - Abdul Kadir, Muhamad Afiq (2017)
The purpose of this correlation research study was to investigate whether a relationship existed between working environment and administrative support staff at IADA Kalaka-Saribas, Saratok. Using a convenience sampling, 104 respondents were involved in the study. The findings showed that furniture has no significant relationship with the administrative support staff’s productivity. The result also showed that lighting had a weak relationship with the administrative support staff’s productivity. However, the findings also revealed that noise and temperature had moderate relationship with the administrative support staff’s productivity.